Formulasi Kebijakan Perubahan Masa Berlaku Paspor Biasa dari 5 (Lima) Tahun Menjadi (10 Tahun) Masa Berlaku Paspor Biasa (Studi Kasus Pengambilan Kebijakan di Direktorat Jenderal Imigrasi) - Hata Galih, Renra; Riau, Dwi Putranto; Rulinawaty, Rulinawaty (LPPM Universitas Ekasakti Padang, 2024)
This research aims to investigate the Directorate General of Immigration's policy formulation regarding the change in passport validity period from 5 years to 10 years, focusing on aspects of agenda setting, policy formulation, implementation, and evaluation. The research method uses a qualitative approach with a case study as the main method, collecting data through observation, in-depth interviews, and documentation from the Directorate General of Immigration for five months. Data analysis was conducted using the Miles and Huberman interactive method. The results show that policy formulation involves the stages of agenda setting to identify problems, policy formulation with in-depth analysis, and the implementation process involving the preparation of action plans and public socialization. A thorough evaluation is conducted to measure the success and impact of the policy, including community compliance and system performance evaluation. The conclusion of this study is that the Directorate General of Immigration's policy formulation process regarding changes in passport validity period demonstrates a strong commitment to transparency, public participation, and policy effectiveness. Nonetheless, the evaluation also identified challenges related to the security and economic impact of the policy. The recommendation for future research is to strengthen the analysis with a quantitative approach for higher validity.